Study on settlement rule and time effect of surrounding rock in diversion tunnel - Tong, Xuewei; Ma, Wenjia; Liu, Haining; Huang, Kai; Su, Kunkun; Yue, Changxu; Wang, Tianyi; Yuan, Jianzhong (Frontiers in Earth Science, 2025)
Currently, challenges such as water gushing, rock bursts, and large deformations persist during diversion tunnel excavation, necessitating the study of surrounding rock stability post-excavation. This paper focuses on the No.1 tunnel of the Xiaolangdi North Bank Irrigation Area project. The settlement of the surface and vault was monitored on site, and a three-dimensional tunnel model was established by FLAC 3D to analyze the displacement evolution law of the key monitoring sections of the surface and vault. Finally, the formula of time effect between surface and vault settlement of tunnel 1# is deduced and verified. Results show: (1) Settlements increase sharply early on, slow later, and stabilize, with arch roof settlement exceeding surface settlement; (2) The arch settlement is generally 2-3 times greater than the surface settlement, both following similar trends in FLAC 3D simulations; (3) The monitoring data were slightly smaller than the simulation data, with the arch roof settlement error ranging from 0.09 mm to 0.72 mm, and surface settlement errors from 0.5 to 3.71 mm; (4) The error rate between the results obtained from the deduced formula and the actual monitoring is between 0.62% and 9.39%, with a surface settlement warning threshold of 10 mm to ensure safe excavation. Discrepancies between simulations and field data likely stem from idealized model assumptions versus real-world geological heterogeneity. The spatio-temporal correlation model can provide quantitative reference for monitoring scheme optimization and disaster warning of similar projects.